2020
DOI: 10.1038/s41380-020-0828-z
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glutamate homeostasis in the nucleus accumbens in human cocaine addiction

Abstract: Cocaine addiction is characterized by overwhelming craving for the substance, which drives its escalating use despite adverse consequences. Animal models suggest a disrupted glutamate homeostasis in the nucleus accumbens to underlie addiction-like behaviour. After chronic administration of cocaine, rodents show decreased levels of accumbal glutamate, whereas drug-seeking reinstatement is associated with enhanced glutamatergic transmission. However, due to technical obstacles, the role of disturbed glutamate ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 42 publications
5
34
0
2
Order By: Relevance
“…The significant reduction in glutamate concentration in the putamen and the low glutamate turnover in patients with CUD is in keeping with previously published findings in CUD, suggesting a substantial downregulation of glutamate neurotransmission, including widespread reduction in glutamate receptors (29,76,77) and low glutamate concentrations (27,30). To the best of our knowledge, our study is the first to show in humans a link between abnormal glutamate turnover and increased automatic habits.…”
Section: Abnormal Glutamate Turnover Predicts Self-reported Habits In Patients With Cudsupporting
confidence: 92%
See 1 more Smart Citation
“…The significant reduction in glutamate concentration in the putamen and the low glutamate turnover in patients with CUD is in keeping with previously published findings in CUD, suggesting a substantial downregulation of glutamate neurotransmission, including widespread reduction in glutamate receptors (29,76,77) and low glutamate concentrations (27,30). To the best of our knowledge, our study is the first to show in humans a link between abnormal glutamate turnover and increased automatic habits.…”
Section: Abnormal Glutamate Turnover Predicts Self-reported Habits In Patients With Cudsupporting
confidence: 92%
“…There appears to be conflicting evidence on changes of these neurotransmitters in cocaine-addicted humans. While some studies suggest either increased (26) or decreased (27,28) cortical levels, subcortical levels of glutamate were either unchanged (29) or reduced (30). These inconsistencies may result from interactions between dopamine and glutamate (31), possibly reflecting individual differences in striatal dopamine depletion due to varying degrees of cocaine use in the samples studied (31).…”
mentioning
confidence: 97%
“…Furthermore, in rodents drug-seeking reinstatement raises extracellular accumbal glutamate levels [14]. In line with animal research, clinical data using tailored proton magnetic resonance spectroscopy demonstrated that people with cocaine use disorder have reduced basal glutamate concentrations and increased glutamate levels in the nucleus accumbens during cueinduced craving [15]. This finding is supported by another proton magnetic resonance spectroscopy trial involving the dorsal anterior cingulate cortex, where glutamate levels were significantly higher in cocaine-dependent patients compared with healthy controls [16].…”
Section: Introductionmentioning
confidence: 75%
“…This report and others (Wang et al, 2010) highlight the important role of NMDAR subunit composition on glutamatergic signalling and reward seeking. In humans, perturbations in glutamate concentration are reported in the NAcb (Engeli et al, 2020) and caudate putamen (Ersche et al, 2020) of substance dependent individuals.…”
Section: Glutamatementioning
confidence: 99%